Design and optimization of quinary high entropy alloy systems with single-phase microstructures from conventional alloy systems - Joseph Agyapong; Yuxin Su; Jatin Chhabra; Aleksander Czekanski; Solomon Boakye-Yiadom (Materials & Design)
High-entropy alloy (HEA) discovery has traditionally relied on theoretical thermodynamic stability criteria and random compositional permutations, often overlooking practical manufacturability and experimental viability. In this study, we present a constraint-driven alloy design framework that enables early-stage development of manufacturable quinary equiatomic HEAs derived directly from conventional engineering alloys. Beyond the classical thermodynamic screening parameters, our framework incorporates manufacturability filters: melting point compatibility (ΔTmc), atomic solubility index, (S¯) and vapor pressure parameter (Pv), targeting additive manufacturing (AM) processability. A flexible web-based platform was developed, allowing users to input any conventional alloy and generate new HEA systems according to the thermodynamic and described criteria. We applied this framework to 15 industrial prototype alloys, generating over 60 quinary HEA candidates, many of which are previously unreported. One predicted composition, CuFeNiMnAl, was successfully fabricated using Directed Energy Deposition (DED), exhibiting a fine-grained FCC structure, high hardness (∼560 HV), and high densification (∼6.8 g/cm3) relative to its parent alloy, nickel aluminum bronze. This experimental validation confirms the framework’s ability to deliver novel, manufacturable HEAs derived from real alloy systems. By integrating manufacturability constraints into HEAs' early-stage design, this work provides a scalable, data-efficient pathway to application-ready HEAs, bridging computational discovery with industrial implementation.